2022
DOI: 10.1111/jebm.12465
|View full text |Cite
|
Sign up to set email alerts
|

Qingjin Yiqi granules for post‐COVID‐19 condition: A randomized clinical trial

Abstract: Objective To evaluate the effectiveness and safety of Qingjin Yiqi granules (QJYQ) on post‐COVID‐19 condition (PCC). Method Patients who met the inclusion criteria were randomly assigned to two groups, the QJYQ group received QJYQ combined with standard rehabilitation treatments (SRTs) and the control group only received SRTs. The treatment course was 14 days. The primary outcomes were modified Medical Research Council (mMRC) scale and Borg scale, while the secondary outcomes included symptoms score and 6‐minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…In the study of Pang et al ( 22 ) the patients used the Borg scale ( 39 ) to grade the level of their fatigue. This is a scale ranging from 0 = nothing at all to 20 = very, very severe (maximal).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Pang et al ( 22 ) the patients used the Borg scale ( 39 ) to grade the level of their fatigue. This is a scale ranging from 0 = nothing at all to 20 = very, very severe (maximal).…”
Section: Resultsmentioning
confidence: 99%
“…Pang et al ( 22 ) used a drug called Qingjin Yiqi granules (QJYQ) for 388 patients with post-COVID-19 fatigue for 14 days. QJYQ contains 16 herbs.…”
Section: Resultsmentioning
confidence: 99%
“…TCM can effectively relieve STC in patients. A randomized controlled trial (RCT) that recruited 388 discharged patients with COVID-19 showed that Qingjin Yiqi granules can improve the STC, in the improved scores of the modified Medical Research Council scale (mMRC) and the Borg scale [ 45 ] . An RCT including 131 convalescent patients showed the evidence that Bufei Huoxue capsule improved the attenuation of pneumonia lesions on chest computed tomography (CT), 6-minute walk distance, and fatigue assessment inventory (FAI) scale [ 46 ] .…”
Section: Interventions For Post Covid-19 Stcmentioning
confidence: 99%
“…A correct system-based history taking and a detailed physical examination will be the starting point of our study. The use of simple scales, such as the Borg or mMRC, will take minimal time and help to quantify the situation 43 , 44 . As a rule, the routine complementary tests performed in these patients are usually normal and show no evidence of organ involvement: lung X-rays and CT scans, echocardiography, and even NT-ProBNP levels do not usually provide pathological findings in persistent patients.…”
Section: Long-term Cardiac Manifestations: Long Covidmentioning
confidence: 99%